Peaking: a revised approach following evidence from the Athens Olympic Games - Issurin, V.; Kaufmann, L.; Lustig, G. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The database for analysis was formed by the results of Olympic swimmers representing nine world-leading National teams; more then 300 events in total. The results were registered by the electronic "Omega" system and were collected from the official protocols of Olympic trials and the Athens Olympic Games. The duration of the time course between the trials and Olympics ranged within 29-130 days. Descriptive statistics and correlation analysis was used. Results and Discussion. The most integrative indicator of the effectiveness of the FSP in different teams is the number of improved trials' performances related to the total number of individual Olympic events for this team. This relation ranges within 42.3% (USA) and 22.6% (Great Britain and Canada). No correlation was found between the duration of FSP and its effectiveness. The average gain of results over the FSP was calculated separately for each team; none of them improved their mean results in the trials, and the average decrease in performances varied between 0.25 and 0.87%. This is in contrast with the outcome of a study, where the effect of taper lasting 3 weeks in the lead-up to the Sydney Olympic Games was evaluated (Mujika et al.,2002). The average improvement of 99 Olympians from different countries was equal to 2.2%. The results of present study results are also inconsistent with many other studies conducted in swimming, running, cycling and triathlon, where the pre-taper results were considerably improved, within of a range 1-6% (e.g., Kubukeli et al., 2002). Thus, the considering fact looks paradoxical: taper, as a relatively short-term phase, enables a substantially improved athletic performance, while the much more prolonged FSP for extremely important competitions did not have a positive effect. This contradiction is based on the fact that the pre-taper results registered in fatigued and low-motivated athletes were compared with real peak-performances, while the "Trials-Olympics" comparison dealt with performances of similar importance and motivation. In fact, the improvement potential of elite athletes cannot reach the level of 3-6%; according to the findings of Pyne et al. (2004) the mean results' improvement in USA and Australian Olympic swimmers over 12 months was equal to 0.9%. As concerned the outcome of present analysis, it looks very pessimistic that the majority of Olympians from the leading sport Nations were unable to improve their performance during the period of extreme concentration and motivation. This failure may have to do with social, psychological and physiological factors, and definitely draws special attention to the structure of the preparation and training design.